Multicomponent Synthesis of Sulfones and Sulfides from Triarylbismuthines and Sodium Metabisulfite in Deep Eutectic Solvents. Issue 23 (27th May 2020) - Saavedra, Beatriz; Marset, Xavier; Guillena, Gabriela; Ramón, Diego J.
Abstract : This study describes a novel and catalyst‐free methodology for the multicomponent synthesis of a broad range of sulfones, disulfides, and sulfides from non‐toxic triarylbismuthines (Ar3 Bi) and sodium metabisulfite (Na2 S2 O5 ) in deep eutectic solvents (DESs). The fine tuning of the DESs properties allowed the solubility of all reagents, enhancing their reactivity, as well as, the recyclability of the reaction medium for at least 5 consecutive cycles. Thus, this versatile strategy uses non‐toxic reagents without the need of metal catalysts in a sustainable solvent, being an interesting alternative to traditional hazardous protocols. Abstract : A novel and catalyst‐free methodology for the multicomponent synthesis of a broad range of sulfones, disulfides, and sulfides from non‐toxic triarylbismuthines (Ar3 Bi) and sodium metabisulfite (Na2 S2 O5 ) in deep eutectic solvents (DESs), has been described for the first time.